PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE - Ariesta Cos Leutualy; Juliana Selvina Molle; Novalin C Huwaa (Science Map Journal, 2020)
This study aims to determine whether there is an increase in learning outcomes of seventh grade students of SMP Negeri 2 Ambon by using the Think Talk Write learning model on the material of One Variable Linear Equations and Inequalities. The subjects in this study were students of class VII-7 SMP Negeri 2 Ambon in the 2019/2020 academic year. This research is a classroom action research (PTK) with a teacher who acts as a teacher and takes place in 2 cycles. Data collection was carried out using tests and observation sheets. The data analysis technique used is quantitative and qualitative data analysis techniques. The results of data analysis show that there is an increase in learning outcomes from cycle I to cycle II, namely in cycle I the percentage of learning outcomes is 50% (15) of students who reach KKM â‰¥ 70 and the percentage of learning outcomes in cycle II is 73.33% (22) students who obtaining the value of student learning outcomes from cycle I to cycle II increased 23.33%. Thus the Think Talk Write (TTW) learning model can improve the learning outcomes of grade VII students of SMP Negeri 2 Ambon on the material of One Variable Linear Equations and Inequalities